A Critical Examination of the Role of Marine Snow and Zooplankton Fecal Pellets in Removing Ocean Surface Microplastic - Kvale, Karin F.; Friederike Prowe, A. E.; Oschlies, Andreas (Frontiers in Marine Science, 2020)
Numerical simulations and emissions estimates of plastic in and to the ocean consistently over-predict the surface inventory, particularly in the case of microplastic (MP), i.e. fragments less than 5 mm in length. Sequestration in the sediments has been both predicted and, to a limited extent, observed. It has been hypothesized that biology may be exporting a significant fraction of surface MP by way of marine snow aggregation and zooplankton faecal pellets. We apply previously published data on MP concentrations in the surface ocean to an earth system model of intermediate complexity to produce a first estimate of the potential global sequestration of MP by marine aggregates, including faecal pellets. We find a MP seafloor export potential of between 7.3E3-4.2E5 metric tons per year, or about 0.06-8.8% of estimated total annual plastic ocean pollution rates. We find that presently, aggregates alone would have the potential to remove most existing surface ocean MP to the seafloor within less than 2 years if pollution ceases. However, the observed accumulation of MP in the surface ocean, despite this high potential rate of removal, suggests that detrital export is an ineffective pathway for permanent MP removal. We theorize a prominent role of MP biological fouling and de-fouling in the rapid recycling of aggregate-associated MP in the upper ocean. We also present an estimate of how the potential detrital MP sink might change into the future, as climate change (and projected increasing MP pollution) alters the marine habitat. The polar regions, and the Arctic in particular, are projected to experience increasing removal rates as export production increases faster than MP pollution. Northern hemisphere subtropical gyres are projected to experience slowing removal rates as stratification and warming decrease export production, and MP pollution increases. However, significant uncertainty accompanies these results.